Explaining A Narrative in The Critical Philosophy of History - Arif Akhyat (Jurnal Filsafat "WISDOM", 2019)
This paper explains the narrative in the study of history which has only been understood as a way of telling what should have happened, not what really happened. Narrative as a philosophical thought will be able to reveal not only the factual side but also the actual side. As a philosophical thought, the narrative should be able to provide a new understanding that narration is not just telling (history as a story), but also how can narration be used to explain the historical actuality? Through a new understanding of narrative, history actually as science becomes parallel to other sciences as philosophy. Historical narratives then present "stories" to "facts explained". Thus, history is present and humane because it is always actual. History as a narrative, thus not only makes history a discourse with a dissertation of evidence but also history as a way of abstracting objects in factual thinking.